Sikap Guru Dalam Pengajaran Sejarah - Siti Rohah, Abdullah (1998)
This research is intended to show how far the teacher-factor is a determiner in the learning and studying of history in secondary schools. Fourteen secondary schools in and around Sungai Petani in Kuala Muda District are chosen for this research. A total of 92 respondents consisting of history teachers are involved in this research. The return has shown a significant relationship between the teacher-factor and the students interest in learning and studying history. Demographic factors such as length of teaching experience of the teacher, the teachers innovativeness in his profession, his attitude and teaching methodology indicate a significant relationship with regards to the students interest in studying and learning the subject. On the other hand , other factors such as the teachers background in relation to his age, sex, school grade and class organisation have not shown any significant relationship with the students enthusiasm for the subject. The data obtained has been analysed using the SPSS programme. Generally, there is a marked significance shown between the methodology factor applied by the teacher and his experience in teaching the subject with the students interest for history. This research has achieved it goals and objectives. Its importance to the school and the Education Department is that it hopes to find an approach that will assist to motivate the history teacher and consequently produce excellent students of history simultaneously discarding the assumption history being a ‘dead subject’. Furthermore, this research is able to provide guideline to the history teacher to evaluate his strengths and weaknesses in teaching the subject and improve himself professionally to help realise the National Education Vision.